Arteterapia e luto: uma revisão integrativa - Junqueira, Fabíola Mancilha (2021)
Mourning tends to show similarities with artistic creation. Both the mourner and the artist about to create face several possibilities for building a new reality and for establishing new relations to the world. The creative process in the context of art therapy may serve as a metaphor that contributes to the understanding of the experience of grief. Therefore, when these processes are lived simultaneously, it is possible that this therapeutic modality will offer the mourner a safe space of free expression and experimentation of feelings and emotions often difficult to share and understand. This study consisted of an integrative review, whose objective was to identify the content of publications that address the use of art therapy as a resource for assisting the mourner and the role that these methods play in the process of elaborating the loss. From the definition of the descriptors for the delimitation of the research, we carried a search in CAPES Portal database, in order to list scientific articles, of a descriptive and qualitative nature, published between years 2016 and 2020. From 312 articles published in English, Portuguese and Spanish, we selected eleven publications, excluding the others since they were studies that did not meet the inclusion criteria adopted. This research revealed that the art therapy process may enable the expression of difficult feelings, often present in the grieving process, and that the presence of the professional art therapist aware of the importance of ethics and familiar with their own mourning processes can contribute to the elaboration of the loss. The understanding of these studies provided a better understanding of the importance of the still incipient sharing of these experiences in scientific journals for the development of the art therapy area in the care of the bereaved. This study was funded in part by Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – Brasil (CAPES) – Funding Code 1548299/2019-06